2021
DOI: 10.1371/journal.ppat.1009088
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptation to human protein kinase R by a unique genomic rearrangement in rhesus cytomegalovirus

Abstract: Cytomegaloviruses (CMVs) are generally unable to cross species barriers, in part because prolonged coevolution with one host species limits their ability to evade restriction factors in other species. However, the limitation in host range is incomplete. For example, rhesus CMV (RhCMV) can replicate in human cells, albeit much less efficiently than in rhesus cells. Previously we reported that the protein kinase R (PKR) antagonist encoded by RhCMV, rTRS1, has limited activity against human PKR but is nonetheless… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…To achieve this, herpesviruses express multiple accessory proteins, many of which are dedicated to the evasion of host restriction factors [ 6 ]. These viral evasion genes display the characteristic evolutionary signatures of ongoing conflict with host defence [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, herpesviruses express multiple accessory proteins, many of which are dedicated to the evasion of host restriction factors [ 6 ]. These viral evasion genes display the characteristic evolutionary signatures of ongoing conflict with host defence [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the mechanisms limiting cross-species infection of cytomegaloviruses are less well understood. For instance, a very recent study reported that the replication of rhesus CMV in human cells is considerably enhanced upon duplication of a terminal genomic region which enhances expression of the protein kinase R (PKR) antagonist rTRS1 encoded by rhesus CMV [ 48 ]. This indicates that translational inhibition instituted by human PKR serves as a barrier against cross-species infection with rhesus CMV, which can be overcome by adaptive gene amplification [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…3), RL13 and ULb' genes lack any obvious frameshift or translation terminating mutations. Adaptation processes of primate CMVs to human cells can occur in a rapid fashion facilitated by recombination events (Child et al, 2021) or by positive selection of advantageous genetic variants (Mozzi et al, 2020). UL48, which exhibits the second highest number of non-synonymous polymorphisms among all CCMV genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of prolonged periods of coevolution, CMVs are highly adapted to their specific hosts, making cross-species infections extremely rare events (Burwitz et al, 2016;Child et al, 2021;Murthy et al, 2019). CMVs are very prevalent in their host populations, due to lifelong, mostly asymptomatic infections.…”
Section: Introductionmentioning
confidence: 99%